Free Latissimus Dorsi Flaps in Head and Neck Reconstruction at a Modern High-Volume Microsurgery Center - Shyaka, Ian; Su, Chun-Lin; Wei, Fu-Chan (Journal of Reconstructive Microsurgery, 2024)
Background Over the past two decades, with the introduction of the perforator flap concept and advances in flap dissections, lower extremities have emerged as the preferred soft tissue flap donor sites. As a modern and high-volume microsurgical center, and the senior author being one of the pioneers and advocates for the use of lower extremity flap donor sites, we aim to investigate the role of latissimus dorsi (LD) free flap in head and neck reconstruction within our current practice.Methods All free LD flaps used for head and neck reconstruction performed by a single surgeon between January 2010 and June 2023 were reviewed for their indications and immediate and short-term outcomes.Results A total of 1,586 head and neck free flap reconstructions were performed, and 33 free LD flaps were identified. The patients' median age was 53 (interquartile range [IQR] 48.5–63.5) years. Twenty-nine (87.9%) flaps were used to reconstruct oro-maxillo-facial and four (12.1%) flaps were used to reconstruct scalp defects. Most patients had prior radiation (n = 28, 84.8%), neck dissection (n = 24, 72.7%), and multiple previous head and neck flap reconstructions with a median of 3.0 (IQR 3.0–3.5) previous flaps. Six (18.2%) LD flaps were used to replace failed flaps from other donor sites. No major complications such as total flap failure or takebacks, and no need for vein grafts but three (9.1%) had flap marginal necrosis. Other complications included one flap dehiscence (3.0%), one orocutaneous fistula (3.0%), two wound infections (6.1%), three plate exposures (9.1%), and three patients who developed local recurrence (9.1%). The median patient follow-up time was 16 (IQR 5–27) months.Conclusion This retrospective study demonstrates the role of LD free flap in head and neck reconstruction as a reliable and versatile backup soft tissue flap when workhorse flaps from lower extremity donor sites are either unavailable or unsuitable.
Keywords: latissimus dorsi free flap; head and neck reconstruction; microsurgical free flap; recurrent head and neck cancers